(untitled) (Global Journal of Management and Business Research, 2024)
The risks that inflation poses to economic growth and stability call for creative solutions. In this essay, we look at how entrepreneurship might help ease economic inflation. The role of entrepreneurs in fostering economic expansion, more employment opportunities, and higher output is explored. The article examines the role of entrepreneurship in promoting innovation, which in turn can lead to the creation of new products and services that improve competition and hence alleviate inflationary pressures. The importance of free markets in containing inflation is also emphasised, with an emphasis placed on the role played by entrepreneurial spirit in fostering an environment where prices are kept low. This article looks at how higher production and more effective resource allocation-both results of entrepreneurship’s impact on the supply side of the economy-help keep inflation in check. Case studies of prosperous businesses that had a beneficial effect on inflation dynamics are used to examine the feasibility of entrepreneurship as a response to high inflation rates. Sensitivity to business cycles, risk and failure, market concentration, and access to financing are only some of the issues that are critically discussed in the context of employing entrepreneurship as a strategy to combat inflation.